Physiological data of Kilian Jornet during the victory of UTMB 2022: An exceptional report of maximal metabolical limits - Álvarez-Herms, J.; Jornet, K. (Sports Medicine, 2024)
We have reviewed the article entitled "Limits of Ultra: Towards an Interdisciplinary Understanding of Ultra-Endurance Running Performance" by Berger et al. [1] with great interest. This article describes the main psychobiological limits of ultraendurance races (UER), specifically explaining concepts such as critical speed and running cost, alongside their correlations with metabolic state, oxygen consumption, energy efficiency, and running motor patterns. According to the authors [1] and our present results, the duration of UER determined metabolic functions, energy efficiency, biomechanics, and the central neural fatigue.